Hippocampal adult-born granule cells drive network activity in a mouse model of chronic temporal lobe epilepsy - F. T. Sparks (Nature Portfolio, 2020)
The dentate gyrus is involved in synchronous discharges and seizures, but its microcircuit functional organization in TLE is unclear. Here, the authors show that interictal discharges recruit specific granule cell ensembles dominated by adult-born immature neurons.